If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(3 + -1x) = -6x + 10 (3 * 8 + -1x * 8) = -6x + 10 (24 + -8x) = -6x + 10 Reorder the terms: 24 + -8x = 10 + -6x Solving 24 + -8x = 10 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 24 + -8x + 6x = 10 + -6x + 6x Combine like terms: -8x + 6x = -2x 24 + -2x = 10 + -6x + 6x Combine like terms: -6x + 6x = 0 24 + -2x = 10 + 0 24 + -2x = 10 Add '-24' to each side of the equation. 24 + -24 + -2x = 10 + -24 Combine like terms: 24 + -24 = 0 0 + -2x = 10 + -24 -2x = 10 + -24 Combine like terms: 10 + -24 = -14 -2x = -14 Divide each side by '-2'. x = 7 Simplifying x = 7
| (3x+4)(3x+2)= | | h=8/9*t-11 | | 2x^3-x^2-21x+18=0 | | 2x^3-x^2-21x+8=0 | | h(t)=8/9*t-11 | | 9x-8=18-3x | | Y-7=3/2(x-3) | | 3(3)+7=5(3)-8 | | 0=-2.7t^2+100 | | 29+2d=87 | | x=1/8ad | | Q/4-2=4 | | -2x(x+6)=-22 | | 9(d-83)=90 | | 9(g+3)=90 | | h(t)=8/9*t-3 | | 1/8n=7 | | w/5-49=54 | | 6x+6=6u+6 | | 11-2p=7 | | 3=3j-9 | | 8=2j-2 | | 4b+7a-7ab-ab^2= | | 7(f+7)=91 | | 8+2b=20 | | 1=r/4-4 | | x^6=0.15 | | 4b+7a-7ab-ab= | | 7x+6y+2z-10=0 | | 4ft*x*(4x+5)= | | 3h+4=2 | | r^4+3r^3-5r^2+r-4=0 |